Pembelajaran Jalur Evakuasi Menggunakan Augmented Reality Pada Jurusan Teknologi Informasi - Harahap Muhammad Fauzan Anwar; Farindika Metandi; Bambang Cahyono (JURNAL VOKASI TEKNIK, 2024)
Learning about evacuation routes in the Department of Information Technology (IT) is still considered monotonous because it is delivered through conventional media such as guidebooks or presentations. Learning evacuation routes using augmented reality (AR) in the IT Department presents information related to occupational health and safety in the form of a 3D application for Android-based smart phones, including information on K3, first aid, fire, personal protective equipment, emergency contacts, and evacuation routes in 3D. This research aims to provide a better and interactive understanding of evacuation routes. The method used is SDLC with agile model and blackbox testing to ensure the application features function properly. The results show that the use of AR significantly improves understanding compared to conventional media and can be used indoors and outdoors with appropriate light intensity and camera distance. In conclusion, learning evacuation routes using AR in the IT Department was built with Unity 3D and Vuforia Engine, and can be used as an interactive learning media and K3 introduction for students and lecturers.